Tough Decisions: Exploring Women's Decisions Following Unintended Pregnancies - Spierling, Tiffany; Shreffler, Karina M. (Frontiers in Sociology, 2018)
Approximately half of all pregnancies are unintended. Many (58%) are carried to term, but a substantial proportion of unintended pregnancies are terminated. In this paper, we draw from qualitative interviews with 33 women who experienced an unintended pregnancy in an effort to examine the meanings women attributed to their pregnancies and to explore how narratives differ for women who chose to continue their pregnancies versus those who opted for termination. Findings from grounded-theory analysis highlight the importance of cognitive appraisal, ability to navigate resources, availability of support, individual values and beliefs, and situational context in women’s decisions to terminate or continue with an unintended pregnancy.